PENGARUH ETIKA AUDITOR, PENGALAMAN AUDITOR DAN MOTIVASI AUDITOR TERHADAP KUALITAS AUDIT (Studi Empiris Kantor Akuntan Publik Kota Padang) - Amran, Elsa Fitri; Selvia, Fitri (Universitas Muhammadiyah Tangerang, 2019)
This study aims to determine the effect of the ethics of auditor, experience of auditors, and motivation of auditors on quality of audits at the public accounting firm in the city of Padang. The sample selection of this study using convenience sampling. The data used are primary data obtained directly from the result of questionnaire distribution, with a sample of 68 respondents. The analytical tool used to test the hypothesis that multiple regression analysis using SPSS 16.0. The results showed that the variable ethics of auditor positive impact on the quality of audits big as 0,000 < 0,05 (sicnificant level), variable experience of auditor positive impact on the quality of audits big as 0,024 < 0,05 (sicnificant level), and variable motivation of auditors positive impact on the quality of audits big as 0,000 < 0,05 (sicnificant level).